Structural equation modeling of the relationship between childhood trauma and sexual addiction with the mediating role of perceived social support, mentalization and attachment styles - mona Adibifar; Mehdi Manouchehri; Afshin Salahian; Bita Nasrollahi (مجله علوم روانشناختی)
Background: Children facing challenges such as social deficiencies during childhood may struggle in social interactions and unhealthy emotional relationships, thus increasing their vulnerability to sexual addiction. The relationship between childhood traumas and sexual addiction is influenced by various factors such as social support, mental framing, and attachment styles, highlighting the importance of thoroughly examining the impact of each of these factors on this relationship. Strong scientific evidence can guide decision-makers in implementing effective measures and policies to prevent childhood traumas and sexual addiction. Aims: The present study aimed to model the structural equations of the relationship between childhood traumas and sexual addiction, with the mediating role of perceived social support, mental framing, and attachment styles. Methods: The current research employed a descriptive correlational approach and structural equation modeling. The statistical population included all virtual students in Tehran universities during the academic year 2021-2022. The sample size was determined to be 322 individuals based on the Klein formula (2011), considering the possibility of dropouts, with 370 individuals ultimately included. Data collection utilized the Childhood Trauma Questionnaire (Bernstein et al., 2003), Sexual Addiction Screening Test (Carnes, 1988), and Adult Attachment Style Questionnaire (Collins & Read, 1990). The gathered data were analyzed using path analysis in LISREL and SPSS software. Results: The research findings indicate significant correlations, confirming the hypothesized correlation between variables for developing the structural equation model (p< 0.05). Conclusion: The relationship between childhood traumas and sexual addiction is influenced by various factors, including social support, mental framing, and attachment styles, underscoring the critical importance of thoroughly investigating the impact of each of these factors on this relationship. Strong scientific evidence can guide decision-makers in implementing effective measures and policies to prevent childhood traumas and sexual addiction.